Ð‘ÐµÐ»ÐºÐ¸-Ð½ÑƒÐºÐ»ÐµÐ°Ñ‚Ð¾Ñ€Ñ‹ Ð±Ð°ÐºÑ‚ÐµÑ€Ð¸Ð°Ð»ÑŒÐ½Ð¾Ð³Ð¾ Ð¿Ñ€Ð¾Ð¸ÑÑ…Ð¾Ð¶Ð´ÐµÐ½Ð¸Ñ. Ð¡Ð¾Ð¾Ð±Ñ‰ÐµÐ½Ð¸Ðµ II. Ð¡Ñ‚Ñ€ÑƒÐºÑ‚ÑƒÑ€Ð° Ð±ÐµÐ»ÐºÐ¾Ð² Ð¸ Ð¸Ñ… Ð³ÐµÐ½Ñ‹ - Gulevsky, A. K.; Relina, L. I. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2010)
The modern data on bacterial proteinaceous nucleators and their encoding genes are analized in the review. The main hypotheses and models of nucleating protein three-dimensional structure are discussed. The information on the nature and role of non-proteinaceous components of bacterial nucleators is presented.